Linguistic Approaches in Teaching History of Science and Technology Courses through a Content Block on Cognitive Sciences - Olga Krasnyak; Mik Fanguy; Elena Tikhonova (National Research University Higher School of Economics, 2016)
History of Science and Technology (HST) courses are increasingly becoming part of core curriculums for undergraduate students due to an increased emphasis on scientific literacy. HST courses should aim to help students gain an understanding of the nature of science and should enable them to reflect epistemologically. The authors suggest teaching HST courses through several interchangeable content blocks, and herein, present the material and discussion topics that they believe should be implemented in a content block on cognitive sciences through a linguistic component. Language has a special meaning for humankind as it indicates its unique ability in the evolutionary development and in creating a new social environment. Therefore, paying special attention to the linguistic component when teaching HST courses helps students obtain a basic level of linguistic knowledge as its interdisciplinary approaches are increased through the study of cognitive sciences such as evolutionary psychology, behavioral genetics, and artificial intelligence. In order to represent a practical meaning of linguistics in the processes of constructing social environment, the authors conducted an empirical study based on the analysis of media texts. We asked 63 sophomores majoring in social sciences and humanities, who are affiliated with the Peoples' Friendship University of Russia and the Moscow State Institute of International Relations to choose 60 media texts, both broadsheets and tabloids, on social and political content. Estimating and analyzing the surveys allowed the authors to determine students' abilities to identify communicative strategies that were used in the media texts, to understand the role of the strategies in forming the social environment of a person or a group, and to recognize how using the tools of cognitive linguistics enhances sophisticated thinking and develops synergetic perceptions of every individual.